2023
DOI: 10.3390/antibiotics12030590
|View full text |Cite
|
Sign up to set email alerts
|

Perchlozone Resistance in Clinical Isolates of Mycobacterium tuberculosis

Abstract: The emergence of drug-resistant tuberculosis forced the development of new drugs and the screening of more effective or less toxic analogues. Mycolic acid biosynthesis is targeted by several antituberculosis drugs, isoniazid being one of the most important in tuberculosis therapy. Recently, perchlozone, acting on another step in the FAS-II cycle, was officially approved for tuberculosis treatment in the Russian Federation and was included in the Russian national clinical guidelines. Using the serial dilution m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
0
0
Order By: Relevance
“…396,397 EthA is also involved in the bioactivation of the thiourea thiocarlide (isoxyl), and the thiosemicarbazones, thioacetazone and perchlozone. 399,400,403 The spiroisoxazoline alpibectir ( 103) is currently being evaluated in a phase 2 trial (NCT05473195) in combination with ethionamide (104) compared to 104 alone in participants with rifampicin-and isoniazid-susceptible pulmonary TB. Nontraditional Small Molecule MoAs: Compounds of Interest.…”
Section: Previous Examples Of Clinical-stage Amps Include the Protegr...mentioning
confidence: 99%
See 1 more Smart Citation
“…396,397 EthA is also involved in the bioactivation of the thiourea thiocarlide (isoxyl), and the thiosemicarbazones, thioacetazone and perchlozone. 399,400,403 The spiroisoxazoline alpibectir ( 103) is currently being evaluated in a phase 2 trial (NCT05473195) in combination with ethionamide (104) compared to 104 alone in participants with rifampicin-and isoniazid-susceptible pulmonary TB. Nontraditional Small Molecule MoAs: Compounds of Interest.…”
Section: Previous Examples Of Clinical-stage Amps Include the Protegr...mentioning
confidence: 99%
“…Ethionamide ( 104 ) is a prodrug that is activated by Baeyer–Villiger monooxygenases such as EthA, initiating formation of an adduct with NADH, which inhibits the enoyl acyl carrier protein reductase InhA leading to disruption of mycolic acid biosynthesis and cell death. However, high concentrations of ethionamide ( 104 ) are usually required, which can lead to side effects, as the expression of ethA is negatively regulated by transcriptional repressor EthR . It was shown that spiroisoxazolines inhibit the repressor EthR, which led to increased levels of EthA and activated ethionamide ( 104 ). , EthA is also involved in the bioactivation of the thiourea thiocarlide (isoxyl), and the thiosemicarbazones, thioacetazone and perchlozone. ,, The spiroisoxazoline alpibectir ( 103 ) is currently being evaluated in a phase 2 trial (NCT05473195) in combination with ethionamide ( 104 ) compared to 104 alone in participants with rifampicin- and isoniazid-susceptible pulmonary TB.…”
Section: Compounds With New Antibacterial Modes Of Actionmentioning
confidence: 99%